Factors determining intention to use mobile banking among clients within Yemeni banks / Ahmed Mohammed Mutahar Almadhwahi - Mutahar AlmadhwahI, Ahmed Mohammed (Institute of Graduate Studies, UiTM, 2018)
A wide range of business opportunities are created via mobile technologies and services. Notwithstanding the availability of technologically advanced mobile devices, mobile banking services have not been widely accepted by banks’ clients. This study aims to examine the major factors that contribute towards clients’ intention to accept and use mobile banking as one of the e-financial services among Yemeni banks. Financial Institutions around the world are looking for the development and keep up to date with emerging technology to stay in the competition range. Banking is one of the sectors that are influenced by the mobile technological advancement. Many researchers have studied and proposed theories and models of technology usage and acceptance in order to predict and explain user behavior with technology considering the rapid change in both technologies and their environments. Based on Technology Acceptance Model (TAM), and integrating The Mental Accounting Theory (MAT), Hierarchy of Effects Model (HOE), Perceived Risk, this study developed and validated a multi-dimensional model, Mobile Banking Technology Model (MBTM), to better understand intention to use mobile banking service among clients within banks in Yemen. Questionnaire survey method was used to collect primary data from individuals who are non-user of mobile banking services in Yemeni banks. Four hundred and eighty-two valid responses were received. Structural Equation Modelling (SEM) via AMOS software was utilized to determine the importance levels of associations and interactions between the factors tested. This research proposed model developed with seven core constructs; perceived risk , perceived ease of use, perceived usefulness, self-efficacy, awareness as independent variables, intention as the dependent variable, perceived value as mediator variables…